2022
DOI: 10.7454/jki.v25i1.1139
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Documentation in Accredited Hospital

Abstract: Nursing documentation is assessed in hospital accreditation because it includes the actions taken and the quality of provided care. Hospital accreditation undergoes three phases consist of preparation, implementation, and post-accreditation. In the post-accreditation phase, there is reduced compliance of workers and nurses. This study determines the quality of nursing documentation at the fully accredited hospital by using descriptive and quantitative research with a retrospective approach. A simple random sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
(24 reference statements)
1
5
0
Order By: Relevance
“…The study overview can be seen in Table 1. [22] 2006b Qn Central registration of nurses [23] 2007 Qn Low QNC is related to negative patient satisfaction [24] 2007 Ql Nurses' empowerment [25] 2007 Qn Burnout has a negative impact to QNC [26] 2009 Qn Low QNC is related to low patient satisfaction [27] 2010 Qn QNC has a relationship with patient satisfaction [28] 2010 Qn Nursing care delivery models predicted quality of care [29] 2012 Qn Training will impact QNC [30] 2012 Qn Nursing perception related to documentation [31] 2012 Qn Nursing care delivery models will impact QNC and increase patient satisfaction [32] 2013 Qn Supervision will increase QNC [33] 2013 Qn Workload has a significant relationship with QNC [34] 2013 Qn i) Period of employment; ii) Training; and iii) Workload [35] 2013 Qn Supervision will increase QNC [36] 2015 Qn QNC impacted patient satisfaction [37] 2015 SR i) Healthcare delivery risk infection; ii) Medication errors; iii) Quality care delivery; and iv) The quality of healthcare overall. [38] 2016 Qn Nurse-physician relationship has a relationship with QNC [39] 2016 Qn Critical thinking influences nurse work [40] 2017 Qn Discharge planning influences QNC [41] 2017 Qn Standard will improve QNC [42] 2017 Qn Nursing rounds will improve QNC [43] 2017 Qn i) Knowledge; ii) ability/skills; iii) education; and iv) gender have relationships with nursing action [44] 2018 Qn Job satisfaction will impact QNC [8] 2018 Qn Turnover impacted QNC [45] 2018 Qn QNC impacted patient satisfaction [46] 2018 Qn Training of Soft Skills Caring will increase competency, that would impact patient satisfaction [47] 2018 Ql Competence [48] 2018 LR It helps nurse work effectively and efficiently for increasing quality [49] 2019 Qn Significant relationship [50] 2019 Qn Insufficient nursing activities could not fulfill the patient needs <...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study overview can be seen in Table 1. [22] 2006b Qn Central registration of nurses [23] 2007 Qn Low QNC is related to negative patient satisfaction [24] 2007 Ql Nurses' empowerment [25] 2007 Qn Burnout has a negative impact to QNC [26] 2009 Qn Low QNC is related to low patient satisfaction [27] 2010 Qn QNC has a relationship with patient satisfaction [28] 2010 Qn Nursing care delivery models predicted quality of care [29] 2012 Qn Training will impact QNC [30] 2012 Qn Nursing perception related to documentation [31] 2012 Qn Nursing care delivery models will impact QNC and increase patient satisfaction [32] 2013 Qn Supervision will increase QNC [33] 2013 Qn Workload has a significant relationship with QNC [34] 2013 Qn i) Period of employment; ii) Training; and iii) Workload [35] 2013 Qn Supervision will increase QNC [36] 2015 Qn QNC impacted patient satisfaction [37] 2015 SR i) Healthcare delivery risk infection; ii) Medication errors; iii) Quality care delivery; and iv) The quality of healthcare overall. [38] 2016 Qn Nurse-physician relationship has a relationship with QNC [39] 2016 Qn Critical thinking influences nurse work [40] 2017 Qn Discharge planning influences QNC [41] 2017 Qn Standard will improve QNC [42] 2017 Qn Nursing rounds will improve QNC [43] 2017 Qn i) Knowledge; ii) ability/skills; iii) education; and iv) gender have relationships with nursing action [44] 2018 Qn Job satisfaction will impact QNC [8] 2018 Qn Turnover impacted QNC [45] 2018 Qn QNC impacted patient satisfaction [46] 2018 Qn Training of Soft Skills Caring will increase competency, that would impact patient satisfaction [47] 2018 Ql Competence [48] 2018 LR It helps nurse work effectively and efficiently for increasing quality [49] 2019 Qn Significant relationship [50] 2019 Qn Insufficient nursing activities could not fulfill the patient needs <...…”
Section: Resultsmentioning
confidence: 99%
“…Job design refers to a job description that includes everything needed to complete the work as described by the position and responsibility. Job design factors were nursing care delivery [20], [31], [51], training needs [21], nurse competencies [46], nursing roles [21], nursing rounds [42] and nursing documentation [23], [29], [30], [40], [48]. In addition, the other important factors came from the nurses that were reported from four studies.…”
Section: Factors Related To Quality Of Carementioning
confidence: 99%
See 1 more Smart Citation
“…Then an assessment is carried out that focuses on patient care during treatment and when the patient is at home, which is then diagnosed until evaluation involving the patient and family. All of the nursing processes must be documented (Purwandari et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to a study by Purwandi et al, which found that Transformational leadership improves nursing documentation self-efficacy the quality of nursing documentation was poor, with an average achievement of 80.81%. 15 Poor quality in nursing documentation was influenced by nurses' self-efficacy.…”
mentioning
confidence: 99%